The management of special job placement agencies (bkk) to improve graduate absorption in the labor market at smk negeri 1 pangandaran and smk negeri 1 padaherang, pangandaran regency - Finsa Muhammad Pratama; Ricky Yoseptry (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This research is motivated by the role of the Special Job Placement Agency (Bursa Kerja Khusus/BKK), which is reinforced by the Regulation of the Minister of Education and Culture Number 34 of 2018 on Vocational-Based Education, emphasizing the importance of integrating education with the business and industrial sectors. Through the BKK, students are expected to gain access to job vacancy information, skills training, and facilitation of recruitment processes by companies. The objective of this study is to describe and analyze the management of BKK at SMKN 1 Pangandaran and SMKN 1 Padaherang in Pangandaran Regency, with a focus on the implementation of the POAC management functions (Planning, Organizing, Actuating, Controlling) in enhancing graduates’ employability. This study employs a descriptive qualitative approach with data collected through interviews, observations, and document analysis. The findings indicate that BKK planning is carried out systematically and based on labor market needs analysis, involving both internal school stakeholders and external partners from the business and industrial sectors. The organizational structure is clearly defined, with task distribution aligned to competencies, ensuring effective and well-directed program implementation. The execution of activities includes career days, soft skills training, CV preparation, interview simulations, industrial visits, and entrepreneurship training. Supervision is conducted regularly through internal evaluations and external monitoring by the Education Office and the Manpower Office, leading to continuous improvement. Despite differences in strategies resulting from geographical conditions and partner industry potential, both BKKs share a common commitment to improving graduates’ employability.